Continuous Renal Replacement Therapy in Critically Ill Children in the Pediatric Intensive Care Unit: A Retrospective Analysis of Real-Life Prescriptions, Complications, and Outcomes - Buccione, Emanuele; Guzzi, Francesco; Colosimo, Denise; Tedesco, Brigida; Romagnoli, Stefano; Ricci, Zaccaria; L'Erario, Manuela; Villa, Gianluca (Frontiers in Pediatrics, 2021)
Introduction: Severe acute kidney injury is a common finding in the Pediatric Intensive Care Unit (PICU), however, Continuous Renal Replacement Therapy (CRRT) is rarely applied in this setting. This study aims to describe our experience in the rate of application of CRRT, patients' clinical characteristics at admission and CRRT initiation, CRRT prescription, predictors of circuit clotting, short- and long-term outcomes. Methods: A 6-year single center retrospective study in a tertiary PICU. Results: Twenty-eight critically ill patients aged 0 to 18 years received CRRT between January 2012 and December 2017 (1.4% of all patients admitted to PICU). Complete clinical and CRRT technical information were available for 23/28 patients for a total of 101 CRRT sessions. CRRT was started, on average, 40 h (20–160) after PICU admission, mostly because of fluid overload. Continuous veno-venous hemodiafiltration and systemic heparinization were applied in 83.2 and 71.3% of sessions, respectively. Fifty-nine sessions (58.4%) were complicated by circuit clotting. At multivariate Cox-regression analysis, vascular access caliber larger than 8 Fr [HR 0.37 (0.19–0.72), p = 0.004] and regional citrate anticoagulation strategy [HR 0.14 (0.03–0.60), p = 0.008] were independent protective factors for clotting. PICU mortality rate was 42.8%, and six survivors developed chronic kidney disease (CKD), within an average follow up of 3.5 years. Conclusions: CRRT is uncommonly applied in our PICU, mostly within 2 days after admission and because of fluid overload. Larger vascular access and citrate anticoagulation are independent protective factors for circuit clotting. Patients' PICU mortality rate is high and survival often complicated by CKD development.